ANTIBIOTICS IN DENTISTRY (Overview) - Taras Bondar (Bogomolets National Medical University, 2020)
The article summarizes the arguments and counter-arguments within the scientific discussion on the use of antibiotics in dentistry. The main purpose of the study is to analyze various clinical situations that require the use of antimicrobial drugs. The research method was based on the study of scientific articles published in the period from 2005 to 2019 and indexed in Ukraine and international databases, as well as a comparison of different recommendations for the appointment of antibiotics in dentistry, published in developed countries. Systematization of literature sources and approaches to solving the problem of prevention and treatment of purulent-inflammatory infections in dentistry has shown that antibiotics used in different countries around the world, converge on the rational and reasonable use of antimicrobial drugs. The vast majority of researchers believe that antibiotics should be used only in recommended situations for patients at risk of developing purulent-inflammatory infections after dental procedures. However, the question of the rational use of both prevention and empirical treatment of infections with antibiotics in dentistry remains unresolved. This is primarily due to the constant change in biological properties, including resistance to antibiotics of pathogens of purulent-inflammatory infections of the oral cavity. Only a few studies are devoted to this topic, and there are no modern data in the available literature. In Ukraine, there are no officially approved recommendations for the use of antibiotics in dentistry. There is also no state-level epidemiological surveillance for resistance to infectious agents, including the oral cavity. In addition, the question of the effectiveness of the use of antibiotics in dentistry has not been studied. Additional research is needed to study the emergence and spread of antimicrobial-resistant microorganisms in health care facilities, including in outpatient settings and the use of antibiotics by dentists, which, according to some international guidelines, seem widespread and not limited to situations that described in the guidelines of associations of dentists in developed countries. Therefore, dentists should be careful in the use of antibiotics, both for the treatment and prevention of infections, and prescribe antibiotics only if recommended by guidelines based on the results of evidence-based medicine, as well as effectively and safely.